A multiscale comprehensive index for evaluating the development level of surface granite discontinuities - Guojun Liu; Xiang Wei; Zhenkun Hou (PLoS ONE, 2025)
The Gansu Beishan area is a preselected candidate site for a high-level radioactive waste repository in China. The development of surface rock mass discontinuities in this region is crucial for ensuring the long-term stability and safety of the project. The survey line method was employed to investigate these discontinuities. Fault geometry information was defined based on the characteristics of traffic routes and exploratory trench wall fault gouge. Optimal joint sets were identified using rose diagram equal-area upper hemisphere projection methods. Statistical analysis shows that the dominant joint orientations in each group follow a normal distribution. Using the circular sampling window theory, the mean trace length and trace midpoint density of joints for each outcrop were calculated. A Multiscale Discontinuity Comprehensive (MDC) index was proposed to evaluate the degree of surface rock mass discontinuity development based on discontinuity geometry parameters. The results of the surface rock mass discontinuity development were analyzed according to the tectonic stress and mechanical formation mechanisms of the discontinuities. These research findings provide critical data to support the ongoing development of high-level radioactive waste geological disposal.